The Role of Product Differentiation, Customer Purchase Intention, and Islamic Self-Congruity in Driving Customer Loyalty - Cavallera, Riyan; Nabhan, Faqih (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Objective: This research aims to examine efforts to encourage the optimization of product differentiation, which can significantly impact customer purchase intention and Islamic self-congruity, thereby enhancing customer loyalty. Research Design & Method: This study was conducted with 150 Shopee customers residing in Salatiga city, utilizing an online questionnaire distributed via WhatsApp (WA) using accidental sampling technique. The collected data were processed using Partial Least Square Program Smart (PLS) Version 4.0, with Variance Based Structural Equation Modeling (SEM). Findings: The results of this research indicate that product differentiation is effective in driving customer purchase intention and Islamic self-congruity but fails to increase customer loyalty. Furthermore, customer purchase intention plays a significant role in boosting customer loyalty. However, Islamic self-congruity does not lead to increased customer loyalty. Implications & Recommendations: This study concludes that higher levels of product differentiation in Muslim clothing offered by Shopee do not directly enhance customer loyalty. Companies need to manage and optimize customer purchase intention to have a more substantial impact on driving customer loyalty. Islamic self-congruity has not successfully leveraged product differentiation in increasing customer loyalty. Contribution & Value Added: This research offers a fresh perspective on self-congruity theory, highlighting that self-congruence based on specific beliefs and religious convictions provides an opportunity for a broader exploration of customer behavior phenomena. Future research would be intriguing if conducted with more heterogeneous respondents, leading to a deeper understanding of the roles of customer purchase intention and Islamic self-congruity in enhancing customer loyalty.